2018
DOI: 10.3390/ijms19103006
|View full text |Cite
|
Sign up to set email alerts
|

Comparison on Photosynthesis and Antioxidant Defense Systems in Wheat with Different Ploidy Levels and Octoploid Triticale

Abstract: To investigate the evolutionary differences of wheat with different ploidy levels and octoploid Triticale, photosynthetic capacity, and antioxidant defenses system were compared within and between diploid, tetraploid and hexaploid wheat, and octoploid Triticale seedlings. The results showed that seed germination rate, chlorophyll content, and photochemical activity of photosystems, and the activities of antioxidative enzymes in hexaploid wheat and octoploid Triticale were significantly higher than in diploid a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 63 publications
3
20
0
Order By: Relevance
“…High fluorescence of state transitions in the compatible system at 120 hpi may be contributed to unbalance the complements of LCHII between PSI and PSII after infection by stripe rust. These findings were further confirmed by the results obtained from the photochemistry of PSI, which is usually shown to be seriously damaged under heavy environmental stresses [52][53][54]. In the present experiment, our results showed that PSI photochemistry significantly decreased after inoculation with Pst compared with the control, and the levels of PSI photochemistry in the compatible system were lower than that of the incompatible system at 48 and 120 hpi ( Figure S5), which suggests that stripe rust infection resulted in the damage to PSI.…”
Section: Discussionsupporting
confidence: 63%
“…High fluorescence of state transitions in the compatible system at 120 hpi may be contributed to unbalance the complements of LCHII between PSI and PSII after infection by stripe rust. These findings were further confirmed by the results obtained from the photochemistry of PSI, which is usually shown to be seriously damaged under heavy environmental stresses [52][53][54]. In the present experiment, our results showed that PSI photochemistry significantly decreased after inoculation with Pst compared with the control, and the levels of PSI photochemistry in the compatible system were lower than that of the incompatible system at 48 and 120 hpi ( Figure S5), which suggests that stripe rust infection resulted in the damage to PSI.…”
Section: Discussionsupporting
confidence: 63%
“…Soluble sugars and proline are well known as the two most important organic solutes and their increase is commonly observed in response to environmental stress. Many studies indicate that evaluation of proline accumulation can be useful in the assessment of drought tolerance in cereals [33].…”
Section: Functioning Of the Oma Line Photosynthetic Apparatus In Droumentioning
confidence: 99%
“…Based on the passive hyperspectral remote sensing technology, studies have been conducted by some scholars to build different models to obtain more accurate biochemical parameter estimation. They proposed different vegetation indices based on statistical analysis models for estimating biochemical parameters or crops yields [10][11][12][13]. However, passive hyperspectral technology is difficult to acquire the spatial information.…”
Section: Introductionmentioning
confidence: 99%